Beyond pain control: Outcome and treatment preferences in pediatric migraine. Issue 5 (6th May 2022) - Khayata, Matthew J.; Farley, Samantha; Davis, J. Kelly; Hornik, Christoph P.; Reeve, Bryce B.; Rikhi, Aruna; Gelfand, Amy A.; Szperka, Christina L.; Kessel, Shirley; Pezzuto, Tara; Hammett, Alex; Lemmon, Monica E.
Abstract: Objective: The objective of this study was to describe treatment preferences and perceived quality of existing outcome measures among children and adolescents with migraine and their caregivers. Background: Across disciplines, there is increasing recognition of the value of direct input from stakeholders. Little empirical work has been done to determine what outcomes matter most to pediatric patients with migraine and their caregivers. Methods: In this qualitative study, we recruited participants from the multicenter, prospective Pediatric Migraine Registry. We used stratified purposive sampling to recruit children and adolescents of varied ages and headache frequency. Patients with migraine and their caregivers completed semistructured interviews targeting treatment preferences and perceived quality of existing outcome measures. Emergent themes and subthemes were identified using conventional content analysis. Results: Thirty dyads of children/adolescents and their caregivers were enrolled and completed 59 interviews ( n = 29 children/adolescent interviews and n = 30 caregiver interviews). Three themes emerged. (1) Symptom relief : Looking beyond headache resolution : Participants described the value of outcomes in addition to pain relief, including a reduction in migraine intensity and improvement in non‐pain symptoms. (2) Trade ‐ offs between side effects and relief : Participants described cost‐benefit analyses that can occur with headache treatment and acknowledged the impact of drug side effects on daily life and medication adherence. (3) Child ‐ centered treatment : Participants described medication attributes salient to the pediatric context, including age‐appropriate routes of administration and adequate safety data. Conclusions: Children, adolescents, and caregivers impacted by migraine value outcomes in addition to traditionally studied migraine endpoints. Participants valued decreased pain severity, even in the absence of pain resolution. Participants also prioritized the absence of side effects and key medication attributes, including fast onset and age‐appropriate routes of administration. These results highlight an opportunity to design patient‐centered clinical trials, develop drugs, and support product labeling that align with the outcomes valued most by children and adolescents with migraine and their caregivers.